Magnesium Isotopes as a Tracer of Crustal Materials in Volcanic Arc Magmas in the Northern Cascade Arc - Brewer, Aaron W.; Teng, Fang-Zhen; Mullen, Emily (Frontiers in Earth Science, 2018)
Fifteen North Cascade Arc basalts and andesites were analyzed for Mg isotopes to investigate the extent and manner of crustal contributions to this magmatic system. The δ26Mg of these samples vary from within the range of ocean island basalts (the lightest being -0.33 ± 0.07‰) to heavier compositions (as heavy as -0.15 ± 0.06‰). The observed range in chemical and isotopic composition is similar to that of other volcanic arcs that have been assessed to date in the circum-pacific subduction zones and in the Caribbean. The heavy Mg isotope compositions are best explained by assimilation and fractional crystallization within the deep continental crust with a possible minor contribution from the addition of subducting slab-derived fluids to the primitive magma. The bulk mixing of sediment into the primitive magma or mantle source and the partial melting of garnet-rich peridotite are unlikely to have produced the observed range of Mg isotope compositions. The results show that Mg isotopes may be a useful tracer of crustal input into a magma, supplementing traditional methods such as radiogenic isotopic and trace element data, particularly in cases in which a high fraction of crustal material has been added.